2015
DOI: 10.1016/j.biopsych.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Induces Brain Region-Specific Alterations of Molecular Rhythms that Correlate with Depression-like Behavior in Mice

Abstract: Background Emerging evidence implicates circadian abnormalities as a component of the pathophysiology of major depressive disorder (MDD). The suprachiasmatic nucleus (SCN) of the hypothalamus coordinates rhythms throughout the brain and body. On a cellular level, rhythms are generated by transcriptional, translational, and post-translational feedback loops of core circadian genes and proteins. In patients with MDD, recent evidence suggests reduced amplitude of molecular rhythms in extra-SCN brain regions. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
101
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(115 citation statements)
references
References 58 publications
10
101
3
1
Order By: Relevance
“…We used p < 0.05 as the significance threshold for all the calculations. M a n u s c r i p t M a n u s c r i p t We measured the bodyweights ( Figure 1A and Figure S2A) and temperatures of the Agg-E mice ( Figure S2B-C) before (pre-stress) and after (post-stress) the 6h 'cage-within-cage' confinement, and the urine markings ( Figure 1B Unlike the bodyweight profile, the body temperature was found to be unrelated to the Agg-E stress ( Figure S2B-C) although other studies have reported the alteration of core body temperature as a consequence of emotional disturbances (41,42). Nevertheless, a significant strain-to-strain difference was registered in the longitudinal alteration of pre-stress temperature of Agg-E mice.…”
Section: Discussionmentioning
confidence: 85%
“…We used p < 0.05 as the significance threshold for all the calculations. M a n u s c r i p t M a n u s c r i p t We measured the bodyweights ( Figure 1A and Figure S2A) and temperatures of the Agg-E mice ( Figure S2B-C) before (pre-stress) and after (post-stress) the 6h 'cage-within-cage' confinement, and the urine markings ( Figure 1B Unlike the bodyweight profile, the body temperature was found to be unrelated to the Agg-E stress ( Figure S2B-C) although other studies have reported the alteration of core body temperature as a consequence of emotional disturbances (41,42). Nevertheless, a significant strain-to-strain difference was registered in the longitudinal alteration of pre-stress temperature of Agg-E mice.…”
Section: Discussionmentioning
confidence: 85%
“…There are also some important contrasts between the in vivo and in vitro observations made by Logan et al (1). When brain areas were studied in vitro ( Figure 5 in Logan et al [1]), the daily oscillations of PER2 luciferase activity were similar in phase and period but exhibited different amplitude oscillations in the SCN and NAc in response to UCMS.…”
Section: Michael Verwey Sherin Al-safadi and Shimon Amirmentioning
confidence: 83%
“…To gain insight into the role of local clock function in UCMS-induced behavioral changes, it will also be important to disrupt the circadian feedback loop in a region-specific manner with Cre-Lox recombination or RNA-interference strategies. Whatever the approach, now that Logan et al (1) have clearly identified behavioral correlates of specific rhythms of clock gene expression in the NAc and SCN, this finding will help to direct future research toward the elucidation of this more general link between circadian rhythms and psychopathology.…”
Section: Michael Verwey Sherin Al-safadi and Shimon Amirmentioning
confidence: 91%
See 2 more Smart Citations